Teaching Reflections about the Architectural Design of the Vocational Training Centers in Granada - Rodríguez, Luis (2016)
If the specificity of the architectural space is considered as a measuring element in the education scope to value the prominence of teaching throughout history, it is worth mentioning that the configuration of the vocational training center as a first-rate education scenario that arrives half century of delay with respect to schools, has few references of very specific period. At present, they continue excessively contaminated because of the continued struggle for linking them with other education levels. This article is focused on this issue. To that end, by interviewing experienced teachers, we value: a) from the most conceptual aspect, elements and architectural spaces that should have those reference centers; b) the appropriateness of the arranged spaces, not only those that meet the regulatory requirements but those that meet the criteria of the centers; c) to the most specific aspects on the way to optimize the arranged space in order to achieve a larger curricular extent. It concludes with a high positive assessment of the opportunity of having the necessary spaces for teaching, relying more strongly on those favoring the free relationship of students and allowing the permeability among the different disciplines that converge in the center.